2003
DOI: 10.1590/s1519-566x2003000400019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an oligophagous insect in relation to the age of the host plant

Abstract: Performance de um Inseto Oligófago em Relação à Idade da Planta Hospedeira RESUMO -A performance de insetos folívoros monófagos e oligófagos deveria ser afetada negativamente pelo envelhecimento das suas plantas hospedeiras. Plutella xylostella L. (Lepidoptera: Yponomeutidae), uma especialista em Cruciferae, foi criada em laboratório com folhas destacadas de repolho (Brassica oleraceae var. capitata). Foram utilizadas a quarta folha expandida de plantas de diferentes idades mais as folhas dos três estratos da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…Between plant age, the oldest leaf (leaf 1) from younger plant have a greater mining sites than on oldest leaf from older plant, which support the assertion that younger leaves are more acceptable for feeding. Previous studies have demonstrated that P. xylostella prefer and perform better on younger leaves which contains high level of nitrogen and proteins (Campos et al, 2003;Campos et al, 2004;Silva & Furlong, 2012;Moreira et al, 2016). Some inactive mining sites by P. xylostella were observed on older leaves (leaf 1 and 2) suggesting that larvae were test feeding or have pre-feeding movement before moving on to a more suitable leaf for mining, as suggested by Silva & Furlong (2012).…”
Section: Oviposition and Feeding Behaviour Of The Diamondback Moth Pmentioning
confidence: 84%
See 4 more Smart Citations
“…Between plant age, the oldest leaf (leaf 1) from younger plant have a greater mining sites than on oldest leaf from older plant, which support the assertion that younger leaves are more acceptable for feeding. Previous studies have demonstrated that P. xylostella prefer and perform better on younger leaves which contains high level of nitrogen and proteins (Campos et al, 2003;Campos et al, 2004;Silva & Furlong, 2012;Moreira et al, 2016). Some inactive mining sites by P. xylostella were observed on older leaves (leaf 1 and 2) suggesting that larvae were test feeding or have pre-feeding movement before moving on to a more suitable leaf for mining, as suggested by Silva & Furlong (2012).…”
Section: Oviposition and Feeding Behaviour Of The Diamondback Moth Pmentioning
confidence: 84%
“…This result is consistent with previous findings where female moths of P. xylostella preferred to lay eggs on younger plants where there was a greater chance of larval survival and development Zhang et al, 2012). Younger plants are considered nutritionally superior over older plants and suitable for offspring performance (Campos et al, 2003;Campos et al, 2004Campos et al, , 2016Coley et al, 2006). Similarly, the intra-plant distribution and the excised leaf experiment showed significant preference for feeding on younger leaves.…”
Section: Oviposition and Feeding Behaviour Of The Diamondback Moth Pmentioning
confidence: 99%
See 3 more Smart Citations